Chemical Component Analysis of Alpinia oxyphylla Miq. Essential Oil and Its Antimicrobial Mechanism against Listeria monocytogenes - HU Xuan, HUANG Ying, WANG Kai, WANG Dan, XIE Xiaoli, ZHAO Jianping, CHEN Xiaolu, YU Fulai (Shipin Kexue, 2024)
In this study, gas chromatography-mass spectrometry (GC-MS) was used to analyze the chemical components of the essential oil extracted from the fruits of Aipinia oxyhylla Miq. (AOEO) by steam distillation. To evaluate the antimicrobial activity of AOEO against Listeria monocytogenes, the inhibitory zone diameter, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by means of filter paper and micro-double dilution methods. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were performed to observe the effect of AOEO on bacterial morphology. The antibacterial mechanism was investigated by measuring the growth curve, the change of electrical conductivity, the leakage of intracellular macromolecules, the activity of superoxide dismutase (SOD) and the content of malondialdehyde (MDA). The results showed that a total of 45 chemical components were identified in AOEO, mainly including terpenes, aromatic hydrocarbons and oxygen-containing derivatives. Among them, valencene, nootkatone, 2,6,10,10-tetramethylbicyclo[7.2.0]undeca-1,6-diene, (2S,4aR,8aR)-4a,8-dimethyl-2-(prop-1-en-2-yl)-1,2,3,4,4a,5,6,8a-octahydronaphthalene, (2R,8R,8aS)-8,8a-dimethyl-2-(prop-1-en-2-yl)-1,2,3,7,8,8a-hexahydronaphthalene and p-cymene were predominant. AOEO significantly inhibited the growth of L. monocytogenes with an inhibitory zone diameter of 14.20 mm. The MIC and MBC were 0.195 and 0.781 mg/mL, respectively. The growth curve showed that the antimicrobial activity of AOEO was concentration-dependent. SEM and TEM showed that AOEO destroyed the morphological structure of L. monocytogenes and changed the permeability of the cell membrane, thereby causing the leakage of a large number of electrolytes and macromolecular contents (nucleic acids and proteins) out of the cells. The dynamic balance of the SOD system was also destroyed by the oil while inducing the generation of a large number of free radicals, thus resulting in increased levels of lipid oxidation and MDA content in the cells. Therefore, AOEO inhibited the growth of L. monocytogenes and causes cell apoptosis by causing a series of cellular changes. This could be due to the synergistic action of multiple components and multiple targets of AOEO. Terpenes, aromatic hydrocarbons and ketones were tentatively identified as the major antibacterial substances of AOEO. This study provides a scientific theoretical basis for the development and utilization of Aipinia oxyhylla Miq. as a natural bacteriostatic agent in the food industry.